Physics beyond colliders: QCD working group report - Dainese, Andrea; Jaeckel, Joerg; Pawlowski, Jan M. (Arxiv, 2019)
This report summarises the main findings of the QCD Working Group in the CERN Physics Beyond Colliders Study.